DESIGN TECHNOLOGY INDIVIDUAL MODEL METHODOLOGICAL TEACHER'S SYSTEMS AS A CONDITION OF HIS PREPARATIONS FOR IMPLEMENTATION DEVELOPING CAPACITY MUSICAL AND PEDAGOGICAL ACTIVITIES (Pedagogy of Higher and Secondary Education, 2022)
No abstract.